2019
DOI: 10.1002/cptc.201900114
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Possibility of Excited State Keto‐Enolate Transformation of the Oxyluciferin‐Luciferase Complex with QM/MM Free Energy Simulations

Abstract: Firefly bioluminescence has been widely studied due to its high quantum yield and its broad range of color modulation, but debates on the origin of its color modulation and the exact chemical form of the emitter are still ongoing. Herein, the ketoenolate transformation of the oxyluciferin-luciferase complex is investigated using quantum mechanics/molecular mechanics (QM/MM) free energy simulations. We find that the free energy profile of this transformation largely depends on the protonation state of the pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 92 publications
1
3
0
Order By: Relevance
“…24 These localized charges not only induce changes in the local electric field of the cavity but are also known to potentially cause conformational changes that can have additional consequences on the local electric field. The local electric field is also heavily affected by the dynamics of the reaction, most notably, the oxyluciferin tautomerization 130 and the decomposition of the dioxetanone. 148 More advanced calculations of the electronic transitions that have utilized QM/MM methods (applying electronic embedding to classical representations) to achieve a better description of the local electric field have concluded that the emission energy of oxyluciferin is red-shifted when the electric field of the luciferase cavity is taken into account.…”
Section: Modeling Of the Electric Field Induced By Pointsupporting
confidence: 86%
See 3 more Smart Citations
“…24 These localized charges not only induce changes in the local electric field of the cavity but are also known to potentially cause conformational changes that can have additional consequences on the local electric field. The local electric field is also heavily affected by the dynamics of the reaction, most notably, the oxyluciferin tautomerization 130 and the decomposition of the dioxetanone. 148 More advanced calculations of the electronic transitions that have utilized QM/MM methods (applying electronic embedding to classical representations) to achieve a better description of the local electric field have concluded that the emission energy of oxyluciferin is red-shifted when the electric field of the luciferase cavity is taken into account.…”
Section: Modeling Of the Electric Field Induced By Pointsupporting
confidence: 86%
“…Another approach used to take into account the non-uniformity of the cavity is to mimic the directionality of the cavity’s polarity by applying a uniform external electric field. , This approach reflects better the fact that the substrate is not free to move in the cavity. In the case of oxyluciferin, the degree of movement in the cavity is limited due to a relatively narrow cavity (for a flat molecule), as can be seen with all classical molecular dynamics simulations perfomed on this system. ,, We remind the reader that a charge q at position P induces at a point M of space at the distance r PM an electric field in the direction PM proportional to q / r PM 2 .…”
Section: Insights From the Calculations Of Oxyluciferin Emissionmentioning
confidence: 95%
See 2 more Smart Citations